Lifestyle of women with neoplastic deasease. Part I. Effects of neoplastic disease on women’s socio-professional performance - Pietryka-Michałowska, Elżbieta; Szymańska, Jolanta; Toruń-Jurkowska, Anna (Polish Journal of Public Health, 2010)
Introduction. Malignant tumours are the second leading cause of death in Poland accounting for 26% of deaths amongst men and 23% of deaths amongst women. In some cases, the disease in question affects professional activities of women. The affected women take early retirement, reduce the working hours or change their jobs into less strenuous. Professional functioning of the affected individuals is hindered to a greater or lesser extent. Aim.The main objective of the present study was to analyse the impact of neoplastic diseases on the socio-professional activity of women and to identify the variables affecting the adopted attitudes. Material and methods. The study involved 331 women diagnosed with neoplastic diseases. The study tool was the questionnaire designed by the authors. Results. The findings have revealed that neoplastic disease significantly changed lives of patients and their families. Moreover, it affects everyday functioning and professional activity of women. The attitudes of women towards socio-professional activity are determined by the type of treatment applied, age, education, place of residence and marital status. It is essential to introduce the mechanisms that are likely to force women to undergo free prophylactic examinations organized by the National Health Fund in the selected health care institutions.